2019
DOI: 10.1016/j.jamcollsurg.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Pain Control Using an Opioid-Sparing Postoperative Pathway

Abstract: BACKGROUND: Opioids are overprescribed after surgical procedures, leading to dependence and diversion into the community. This can be mitigated by evidence-based prescribing practices. We investigated the feasibility of an opioid-sparing pain management strategy after surgical procedures. STUDY DESIGN: Patients undergoing 6 procedures were offered the opportunity to participate in an opioidsparing pain management pathway. Patients were advised to use acetaminophen and ibuprofen, and were provided with a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 23 publications
4
88
0
Order By: Relevance
“…3,6 Several initiatives have now shown that surgical providers can prescribe fewer opioids at discharge without consequences of increased patient suffering or requests for refills. [7][8][9] These cliniciantargeted strategies, such as decreasing the default prescription quantities in the electronic health record and grand rounds presentations, have resulted in decreases in the prescribing of opioids postoperatively. 9,10 Although decreasing the prescribing of opioids is important, decreasing the amount of opioids actually used by patients and disposing of any excess pills after an operation would have further beneficial effects on decreasing unintended chronic opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Several initiatives have now shown that surgical providers can prescribe fewer opioids at discharge without consequences of increased patient suffering or requests for refills. [7][8][9] These cliniciantargeted strategies, such as decreasing the default prescription quantities in the electronic health record and grand rounds presentations, have resulted in decreases in the prescribing of opioids postoperatively. 9,10 Although decreasing the prescribing of opioids is important, decreasing the amount of opioids actually used by patients and disposing of any excess pills after an operation would have further beneficial effects on decreasing unintended chronic opioid use.…”
Section: Introductionmentioning
confidence: 99%
“… 47 Oral administration has been reproducibly demonstrated to be effective for preoperative and postoperative analgesia, specifically. 36 , 48 , 49 Oral dosage protocols range from 650 to 1000 mg and favor “around-the-clock” administration, typically every 6 hours. There have been no high-level studies comparing the effectiveness of dosage differences for the indication of perioperative pain management.…”
Section: Acetaminophenmentioning
confidence: 99%
“… 65 Unfortunately, a recent review of prescribing practices in plastic surgery notes that only 45% and 37% of surgeons report routinely counseling their patients on the risks of addiction and secure medication storage, respectively. 48 …”
Section: What Patients Should Knowmentioning
confidence: 99%
“…Opioid use decreased by 72% with an opioid-sparing pathway and opioid-naïve patients experienced positive outcomes with high satisfaction (Hallway et al, Meyer et al, 2018;Zhou et al, 2017). Specifically, evidence showed an opioid-sparing pathway reduced median postoperative opioid use to ten pills or less (average of four pills) in 98% of patients (Hallway et al, 2019).…”
Section: Evidence Search Results and Evaluationmentioning
confidence: 99%
“…Opioid-sparing techniques may also result in no postoperative opioid use when patients utilize a combination of acetaminophen and ibuprofen (Hallway et al, 2019). One narrative review found multimodal techniques significantly improved postoperative pain scores but specifically showed opioid-free analgesia had the highest patient and surgeon satisfaction (Nassif & Miller, 2018).…”
Section: Evidence Search Results and Evaluationmentioning
confidence: 99%